SOURCE, ATTENUATION AND SITE RESPONSE PARAMETER ESTIMATION IN SUNDA STRAIT AND WESTERN JAVA USING GAUSSNEWTON INVERSION METHOD - Ulil Albab, Muhammad
Spectrum displacement of earthquakes recorded by BMKG on 10 sites covering the Sunda Strait and the Western part of Java are modeled as the product of source, propagation, and site terms. We use an iterative Gauss-Newton inversion to solve the nonlinear problem by using partial derivative on these different terms. This can be done easlity by converting the data in logarithmic form. After convergence, we finally linearize the problem around the solution. We analyze 30 earthquakes event from 2009 – 2010 which featured local magnitudes in the range of 3.8 – 5.8, and hypocentral distance in the range of 50-500 km. This waveform is transformed into the displacement spectrum by using FFT and integration in the frequency domain. a bandpass filter is applied with 0.5-12. Hz range. Assumes Brune's source model, and geometrical spreading in the form of ?????????, ???? is constant. And the Quality factor which frequency dependant in the form ???? = ????0 × ???????? . The results, we acquire the geometrical spreading factor around 1.143, and anelastic attenuation exhibits low Q0 (158.06) and anelastic decay factor (1.23). The computed moment magnitudes are similar to the local magnitudes, and logarithmic of corner frequencies decrease linearly with magnitude according to ????????????10(???????? ) = 1.317(±0.12) ? 0.198(±0.01) × ????????. Finally, site effect response on 10 sites derived from the inversion may be a good reference to amplification on shallow subsurface.